Latin American Challenges to Food Sovereignty From a Constititutional Approach - Pablo Ricardo Mendoza; Frank Luis Mila Maldonado; Karla Ayerim Yanez Yanez (Ius Humani. Jornal do direito, 2023)
Food sovereignty has been addressed from the normative and jurisprudence; However, it is necessary to understand its scope from the internal constitutional in the Latin American region; all this, based on the new paradigm that supposes the conjunction of the agrarian, the food and the environmental within the concept of timely and equitable access to safe food. This led to the analysis of its legal nature as a principle or as a fundamental right from public international law and Latin American Constitutional Law nurtured by Good Living, contrasted with the sustainable development model. From a qualitative documentary research, it was possible to conclude that food sovereignty is defined transversally; however, the mechanisms for its observance do not have State effectiveness in regard to its necessary elements such as opportunity and safety. In Latin America, elements of the rights of peoples are incorporated from the Sumak Kawsay.